94 Mid-wall fibrosis and outcomes in non-ischaemic cardiomyopathy and cardiac resynchronisation therapy. (May 2019) - Shamsi, Aamir; Voon, Victor; Lau, Wai-Yan; Pereira, Helder; Shanmugam, Nesan; Ray, Robin; Anderson, Lisa
Abstract : Background: Non-ischaemic cardiomyopathy has been associated with better left ventricular (LV) remodelling and outcomes post-cardiac resynchronisation therapy (CRT) but has separately been linked to poorer outcomes when associated with mid-wall fibrosis (MWF) on cardiac magnetic resonance. Therefore, we aimed to confirm the impact of MWF in patients with non-ischaemic cardiomyopathy and CRT. Methods: We retrospectively evaluated data from 164 consecutive patients with a diagnosis of non-ischaemic cardiomyopathy and CRT implants. Non-eligible patients were excluded (eg. ischaemic, amyloid or sarcoid cardiomyopathy, missing data). Patients with or without mid wall fibrosis (MWF+, n=69 vs MWF-, n=99), were compared and evaluated for major cardiovascular event (including all-cause mortality or hospitalizations for ventricular arrthythmias, heart failure or myocardial infarction) from time of CRT implant. Results were reported as mean ± SD. p≤0.05 was deemed statistically significant. Results: Mean age of patient cohort was 66 ± 14 years with total follow-up duration of 1140 ± 1018 days. Between the groups, no significant difference in baseline demographics was observed in terms of age, gender, comorbidities (hypertension/diabetes), medication profiles, electrocardiographic measures (intrinsic rhythm and QRS duration). MWF+ demonstrated lower LV ejection fraction (28 ± 10 vs 31 ± 13%, p=0.02) and higher LV end-systolic volume (211 ± 90 vs. 181 ± 96 ml, p=0.05) when compared to MWF-. However, there were no significant differences between MWF+ vs MWF- in terms of all-cause mortality (34% vs 24%, see Figure 1), or hospitalisations for ventricular arrhythmia (5% vs 2%) or heart failure (18% vs 22%), respectively. Conclusion: This retrospective study demonstrated that MWF+ was associated with lower LV ejection fraction and higher LV end-systolic volumes compared to MWF-. However, we observed no significant between-group diferrence in major adverse cardiovascular events. Further evaluation of this patient cohort in larger studies is warranted. Conflict of Interest: Nil